Saul Bellow. - Rovit, Earl H. (University of Minnesota pamphlets on American writers, 1967)
Saul Bellow - American Writers 65 was first published in 1967. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.